2004
DOI: 10.2527/2004.8272185x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of field pea level on intake, digestion, microbial efficiency, ruminal fermentation, and in situ disappearance in beef steers fed forage-based diets

Abstract: Four ruminally and duodenally cannulated crossbred beef steers (397+/-55 kg initial BW) were used in a 4 x 4 Latin square to evaluate the effects of increasing level of field pea supplementation on intake, digestion, microbial efficiency, ruminal fermentation, and in situ disappearance in steers fed moderate-quality (8.0% CP, DM basis) grass hay. Basal diets, offered ad libitum twice daily, consisted of chopped (15.2-cm screen) grass hay. Supplements were 0, 0.81, 1.62, and 2.43 kg (DM basis) per steer daily o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In our study, ruminal pH was decreased with addition of supplement; however, forage digestibility was not affected. Reed et al (2004a) reported similar results with a decreased ruminal pH with increasing levels of field peas in beef steers fed forage-based diets, however forage digestion was not decreased with the inclusion of field peas. Reed et al (2004a) attributed those results to lower starch and higher degraded intake protein levels than traditional cereal grains, such as corn.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…In our study, ruminal pH was decreased with addition of supplement; however, forage digestibility was not affected. Reed et al (2004a) reported similar results with a decreased ruminal pH with increasing levels of field peas in beef steers fed forage-based diets, however forage digestion was not decreased with the inclusion of field peas. Reed et al (2004a) attributed those results to lower starch and higher degraded intake protein levels than traditional cereal grains, such as corn.…”
Section: Methodssupporting
confidence: 60%
“…Although grown primarily as a human food, a potential use for field peas is livestock feed (Reed et al, 2004a,b;Soto-Navarro et al, 2004). The energy content of field peas is similar to corn or other cereal grains, whereas the protein content is approximately 25% (NRC, 1984) and the starch content is 47% compared with other cereal grains (Reed et al, 2004a).…”
mentioning
confidence: 99%
“…Supplemental treatments (1,040 g of DM/hd daily) were control (no supplement) or low, medium, or high levels of UIP (the supplements provided 8.3, 203.8, and 422.2 g of UIP/d and 257.9, 229.8, and 199.7 g of degradable intake protein/d, respectively). Reed et al (2004) reported increased apparent and true ruminal N disappearance and apparent total tract N disappearance with increasing level of field pea supplementation in 8% CP grass hay diets. Field peas were fed at 0, 0.81, 1.62, and 2.43 kg/d and provided approximately 0, 41.7, 83, and 125 g/d of UIP and 0, 148, 296, and 442 g/d of DIP, respectively (Reed et al, 2004).…”
mentioning
confidence: 93%
“…Reed et al (2004) reported increased apparent and true ruminal N disappearance and apparent total tract N disappearance with increasing level of field pea supplementation in 8% CP grass hay diets. Field peas were fed at 0, 0.81, 1.62, and 2.43 kg/d and provided approximately 0, 41.7, 83, and 125 g/d of UIP and 0, 148, 296, and 442 g/d of DIP, respectively (Reed et al, 2004). Köster et al (1996) reported a quadratic increase in apparent ruminal N digestibility with the addition of DIP to low-quality hay diets.…”
mentioning
confidence: 93%
See 1 more Smart Citation